Unscrambling the scramble: Africa's partition reconsidered - Phimister, Ian (My University, 1992)
Studies of the Scramble for Africa agree on very little beyond the fact that the topic is immensely broad and extremely complex. For all that the last decades of the 19th century have been the most closely examined period of Africa's past, there is agreement neither about what is meant by imperialism generally, nor about the causes of Africa's partition specifically. 'The growth of knowledge', Peter Cain and Tony Hopkins have commented, 'has brought less, and not more, coherence to historical understanding'. Indeed, the apparently intractable nature of the process of Partition is underscored in numerous warnings to the unwary to stay clear. Some ten years ago, Bernard Porter darkly observed that the whole question was 'bedevilled with misunderstandings and confusions and crosspurposes'. ‘An always somewhat treacherous field’, he wrote, has been ‘churned into a quagmire’. Nor are more recent conclusions any more sangine. Although 'specific points of agreement will undoubtedly appear - such as the inapplicability of the Hobsonian model, or the economic bases for annexation in West Africa', it is unrealistic, according to James Sturgis, 'to expect that any overall consensus regarding the new imperialism will ever prove acceptable'. Yet however sensible and timely such warnings, they do little to assuage an equally widespread feeling that the retreat from generalisation has turned into a rout. To take only a few examples, Andrew Porter for one has remarked that the ‘gathering of more knowledge from particular and local studies often does comparatively little to advance general understanding’, while Barrie Ratcliffe for another, has pointed to the growing danger that 'area and case studies will replace ... analysis of the Partition as a whole, and that concern with complexity will win out over the need to explain. It cannot suffice to claim that the Partition was but the consequence of the convergence of many different chains of events'. 'It is surely not unreasonable1, Robin Law has argued, 'to expect that the enormous volume of scholarly work on the historical problem of European imperialism which has appeared during the last two decades, should have led to the refinement of theoretical models as well as to the accumulation of detailed facts, to greater understanding rather than to despair at the complexity and difficulty of it all'. While readily acknowledging the impossibility of reaching any consensus which would satisfy even the majority of scholars in such a bitterly contested field, this paper nonetheless attempts to meet the 'reasonable expectations' of at least some of them. It does so by immediately distinguishing between the territorial expansion of empire ('colonialism'), and imperialism (the monopoly stage of capitalism), after which it proceeds, very briefly, to outline the main historiographical developments in the study of Africa's Partition over the last 30 years or so, before suggesting, at greater length, how an alternative explanation might be constructed.
African Studies Seminar series. Paper presented 17 August 1992
Keywords: Imperialism; Africa. Colonization. History; Africa. History